At the Cutting Edge of Halftone Printing: William Augustus Leggo and George Edward Desbarats - Addleman-Frankel, Kate (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2022)
In Canada, halftone photographic images began to feature regularly in the visual landscape of the news in late 1869, almost three decades earlier than anywhere else. In the technologically obsessed world of nineteenth-century photography, that is a huge amount of time by which to lead on a meaningful techno-cultural advance. Behind this early development were William Augustus Leggo (1830–1915) and George Edward Desbarats (1838–1893) and their initial media ventures: the Canadian Illustrated News and its French-language counterpart, L’Opinion publique. Their ground-breaking work to incorporate photographs into the news, and the scant acknowledgment it has received, is the focus of the present article.